EFFECTS OF INTRAUTERINE LOW-DOSE CHLORPYRIFOS POISONING ON POSTNATAL DEVELOPMENT OF OFFSPRING - Dzhumaniyazov Shavkat Atanazarovich (Journal of Science in Medicine and Life, 2024)
The article presents the results of a study of the hypothalamic-pituitary neurosecretory system in the offspring of rats antenatally induced by the organophosphorus pesticide chlorpyrifos. It is indicated that the effect of chlorpyrifos on rats themselves during different periods of pregnancy and lactation causes various dose-dependent and time-dependent effects on the changes in the morphofunctional characteristics of the HPA axis. Disturbances in the development of the neuroendocrine system that arise in the antenatal period of ontogenesis have long-term negative consequences in postnatal life, as evidenced by the growth retardation of experimental rats, late observation, and high mortality due to antenatal disease.